Clinical value of alarm features for colorectal cancer: a meta-analysis - Frazzoni, Leonardo; Laterza, Liboria; La Marca, Marina; Zagari, Rocco Maurizio; Radaelli, Franco; Hassan, Cesare; Repici, Alessandro; Facciorusso, Antonio; Gkolfakis, Paraskevas; Spada, Cristiano; Triantafyllou, Konstantinos; Bazzoli, Franco; Dinis-Ribeiro, Mario; Fuccio, Lorenzo (Endoscopy, 2023)
Background Colorectal cancer (CRC) is a common neoplasm in Western countries. Prioritizing access to colonoscopy appears of critical relevance. Alarm features are considered to increase the likelihood of CRC. Our aim was to assess the diagnostic performance of alarm features for CRC diagnosis.Methods We performed a systematic review and meta-analysis of studies reporting the diagnostic accuracy of alarm features (rectal bleeding, anemia, change in bowel habit, and weight loss) for CRC, published up to September 2021. Colonoscopy was required as the reference diagnostic test. Diagnostic accuracy measures were pooled by a bivariate mixed-effects regression model. The number needed to scope (NNS; i. e. the number of patients who need to undergo colonoscopy to diagnose one CRC) according to each alarm feature was calculated.Results 31 studies with 45 100 patients (mean age 31–88 years; men 36 %–63 %) were included. The prevalence of CRC ranged from 0.2 % to 22 %. Sensitivity was suboptimal, ranging from 12.4 % for weight loss to 49 % for rectal bleeding, whereas specificity ranged from 69.8 % for rectal bleeding to 91.9 % for weight loss. Taken individually, rectal bleeding and anemia would be the only practical alarm features mandating colonoscopy (NNS 5.3 and 6.7, respectively).Conclusions When considered independently, alarm features have variable accuracy for CRC, given the high heterogeneity of study populations reflected by wide variability in CRC prevalence. Rectal bleeding and anemia are the most practical to select patients for colonoscopy. Integration of alarm features in a comprehensive evaluation of patients should be considered.